Predicting the future distribution of Astraeus spp. in Thailand under climate change scenarios using MaxEnt modeling - RUNCHIDA KHUNKRAI; WARONG SUKSAVATE; CHATCHAI NGERNSAENGSARUAY; MINGKWAN NIPITWATTANAPHON; BARAMEE SAKOLRAK; CHERDCHAI PHOSRI; LEELA NAKPONG; KANTIDA BUNLERLERD; THARNRAT KAEWGRAJANG (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Khunkrai R, Suksavate W, Ngernsaengsaruay C, Nipitwattanaphon M, Sakolrak B, Phosri C, Nakpong L, Bunlerlerd K, Kaewgrajang T. 2025. Predicting the future distribution of Astraeus spp. in Thailand under climate change scenarios using MaxEnt modeling. Biodiversitas 26: 4662-4674. Climate change poses a significant threat to global biodiversity by altering species distributions, disrupting ecological interactions, and transforming habitat suitability. This study investigates the potential impact of climate change on three ectomycorrhizal fungi species from the genus Astraeus—A. asiaticus, A. odoratus, and A. sirindhorniae—which form critical symbiotic relationships with tree species, particularly members of the Dipterocarpaceae family. These fungi contribute to forest ecosystem health by enhancing nutrient and water uptake in host plants and have considerable economic and medicinal value due to their edibility and pharmacological properties. Species Distribution Models (SDMs) were constructed using MaxEnt to predict the current and future potential distribution of the three Astraeus species in Thailand under three climate change scenarios: SSP1-2.6 (low emissions), SSP2-4.5 (intermediate), and SSP5-8.5 (high), for two periods, 2021-2040 and 2041-2060. The models incorporated key environmental variables, including tree cover, precipitation during the wettest month, and temperature range. The MaxEnt models demonstrated acceptable predictive performance, with AUC values ranging from 0.686 to 0.799. The most influential predictors were precipitation during the wettest month (Bio13) and tree cover. The results indicated that A. asiaticus currently occupies high-suitability habitats predominantly in northern Thailand and would have a relatively stable distribution with localized fluctuations. In contrast, A. odoratus and A. sirindhorniae are projected to experience pronounced reductions in high-suitability areas. By 2041-2060, under SSP5-8.5, suitable habitats for A. odoratus and A. sirindhorniae are expected to decline by approximately 69.02% and 87.59%, respectively. These reductions are associated with shifts from high-moisture to low-moisture forest types driven by rising temperatures and reduced precipitation. These findings highlight the importance of adaptive conservation strategies, including protecting suitable habitats, restoring degraded forests, and integrating climate-resilient forest management practices.